An introduction to electrical discharge machining (EDM) - Khan, Ahsan Ali; Mohammed, Baba Ndaliman (International Islamic University Malaysia, 2011)
Abstract. The fundamental features of electrical discharge machining (EDM) were discussed in this chapter. The machining principle and its outcomes were highlighted in this chapter. The input variable of EDM presented here are electrical and non-electrical ones. The output of EDM process are given in terms of the material removal rate (MRR), tool wear rate (TWR) and the surface integrity. This chapter is concluded with a discussion on types of EDM. The various types presented here include: the die sinking type, the wire-cut, micro and the dry EDM.